Benthic Foraminifera in Arctic Methane Hydrate Bearing Sediments - Dessandier, Pierre-Antoine; Borrelli, Chiara; Kalenitchenko, Dimitri; Panieri, Giuliana (Frontiers in Marine Science, 2019)
Benthic foraminifera have been widely used as proxy for paleo-methane emissions, mainly based on their stable isotopic signature. In cold seeps, the ecology of these organisms remains uncertain, in particular their ability to thrive during active phases of seepage. In this study, we evaluate the benthic foraminiferal response to methane seepage in Arctic sediments. We do so by examining living and dead benthic foraminiferal assemblages (>63 µm) of 11 push cores collected in two of the most active pockmarks (Lunde and Lomvi) along Vestnesa Ridge, offshore western Svalbard. Benthic foraminiferal assemblages are interpreted in the context of sediment geochemistry, seafloor images, and pore water analyses, which are used to characterize the different microhabitats. At the sampling locations, methane is currently being released making these the ideal sites to investigate the connection between the benthic foraminiferal distribution and methane seepage in the Arctic Ocean. Our results show that benthic calcareous foraminifera live in methane charged sediments, even if the faunal density and diversity is low. We note that the eutrophic-tolerant species Melonis barleeanus withstand the methane-induced hostile geochemical conditions and that it seems to prosper on the additional food availability represented by microbial mats growing at methane seeps. We also observe that the methane transport mechanisms affect different species differently. For example, sediments characterized by advectivelike conditions are distinguished by a high density of living individuals, dominated by Cassidulina neoteretis, whereas sediments characterized by methane diffusion exhibit a very low faunal density. Agglutinated foraminifera are less abundant in sediments influenced by methane seepage, suggesting that this group of foraminifera does not tolerate the geochemical conditions at seeps. A comparison between the size fractions >63 and >125 µm highlights the importance of studying the finer size fraction for ecological studies in ...